ANALYSIS OF IMPACT OF YIELD, INTEREST RATES, U.S FED RATES, AND INFLATION ON PRICE OF GOVERNMENT BONDS IN INDONESIA - Siahaan, Antonius; Panahatan, Julius Peter (Academic Research and Community Services, 2019)
Global factors are increasingly important as a cause of international capital flows. It is almost impossible for emerging markets to protect themselves from external influences on their financial markets. Indonesia as emerging market is influenced by some monetary policies adopted by the U.S Federal Reserve Bank. The plan of tapering and Fed rate increase adopted by the Federal Reserve Bank in the last three years made local currencies turned into the depreciation stage, increasing capital outflow from emerging markets. It created huge impact on government bond prices in Indonesia and can be seen through the relationship of some factors with bond prices. This research analyzes the impacts of BI rates, Fed rates, and inflation rates on six government bonds classified into three periods during November 2013 to October 2016 when tapering and Fed rates became critical issues. It finds that in all periods bond prices are significantly influenced by only BI rates, but BI rates, Fed rates and inflation rate have negative effect on bond prices during the observation period.